The examination of medical errors based on common methodological approaches of forensic medical examination - O. Yu. Aleksandrova; Yu. E. Kuznetsova (Сеченовский вестник)
Proceedings in medical cases use the results of medical examinations: forensic expertise and quality of care expertise. Nowadays forensic experts and quality experts use different notions, various criteria for evaluating actions of professionals and the criteria for assessing the quality of medical care. The lack of common approaches to the analysis of adverse effects in medical practice stands as one of the main factors leading to different points of view in assessing the actions of medical staff in the court.